Novel murine model reveals an early role for pertussis toxin in disrupting neonatal immunity to Bordetella pertussis - Sedney, Colleen J.; Caulfield, Amanda; Dewan, Kaylan K.; Blas-Machado, Uriel; Callender, Maiya; Manley, Nancy R.; Harvill, Eric T. (Frontiers in Immunology, 2023)
The increased susceptibility of neonates to specific pathogens has previously been attributed to an underdeveloped immune system. More recent data suggest neonates have effective protection against most pathogens but are particularly susceptible to those that target immune functions specific to neonates. Bordetella pertussis (Bp), the causative agent of “whooping cough”, causes more serious disease in infants attributed to its production of pertussis toxin (PTx), although the neonate-specific immune functions it targets remain unknown. Problematically, the rapid development of adult immunity in mice has confounded our ability to study the interaction of this agent with neonatal immune components, such as virtual memory T cells which are prominent prior to the maturation of the thymus. Here, we examine the rapid change in susceptibility of young mice and define a period from five- to eight-days-old during which mice are much more susceptible to Bp than mice even a couple days older. These more narrowly defined “neonatal” mice display significantly increased susceptibility to wild type Bp but very rapidly and effectively respond to and control Bp lacking PTx, more rapidly even than adult mice. Thus, PTx efficiently blocks some very effective form(s) of neonatal protective immunity, potentially providing a tool to better understand the neonatal immune system. The rapid clearance of the PTx mutant correlates with the early accumulation of neutrophils and T cells and suggests a role for PTx in disrupting their accumulation. These results demonstrate a striking age-dependent response to Bp, define an early age of extreme susceptibility to Bp, and demonstrate that the neonatal response can be more efficient than the adult response in eliminating bacteria from the lungs, but these neonatal functions are substantially blocked by PTx. This refined definition of “neonatal” mice may be useful in the study of other pathogens that primarily infect neonates, and PTx may prove a particularly valuable tool for probing the poorly understood neonatal immune system.